Effect of Filler Nature on Chemical Resistance and Microhardness of Epoxy Composite Films - Martinyuk, G.; Aksimentyeva, O.; Skoreiko, N.; Zakordonskyi, V. (Physics and Chemistry of Solid State, 2015)
We investigated the processes of water absorption, chemical stability and microhardness of films of epoxy composites that contained as the polymer matrix the epoxy resin UP-655 and mineral fillers: graphite, mica, aluminum oxide at their content (0 - 30 % mass). It found that introduction of mineral fillers significantly affects on all complex of operating characteristics of the films. Increase of filler content, especially mica, to 20 %, resulting in slower process and reducing the quantity of absorbed moisture by films. In the study of physical and mechanical properties of filled epoxy composites was established that the introduction of mineral filler significantly affects their microhardness, and the nature of the exposure is determined by the type and filler content.